Poster: We Are Well: Wayapa movement - Geraldine Burke; Priscilla Pettengell; Chris Hanger (2023)
The poster, 'We Are Well: Wayapa movement ’ is part of a suite of posters that document the 'We Are Well: Intergenerational art-moving-well-being' project. It showcases Aunty Karan leading Wayapa movement with children, Monash students, older community members, teachers and researchers. Poster text: Thanks, Aunty Karan. I love moving with the grass under my bare feet and feeling like wind, like lightning, like the eels, and more. I feel so special and connected to the land. Poster Authors: Geraldine Burke, Priscilla Pettengell, Chris Hanger Photography: Geraldine Burke, Megan Adams, Aislinn Lalor, Chris Hange r Project Acknowledgments: The We Are Well: Intergenerational art-moving-well-being research team Dr Geraldine Burke, Assoc Prof Megan Adams, Assoc Prof Laura Alfrey, Dr Aislinn Lalor, Prof Keith Hill, and Priscilla Pettengell with artists: Nikki Browne, Bidjara artist and educator, and First Nations Learning and Programs Manager, McClelland Sculpture Park and Gallery, Aunty Karan Kent, Bidjara Elder. Founder of Yimba Yumba — in sync with nature through the art of sharing Wayapa Wuurrk, Kylie Colemane, Darug, and Wiradjuri First Nations consultant, artist, and educator. Founder of Your Green Prescription, Kursty Colemane, Darug, and Wiradjuri First Nations knowledge holder, artist, and educator.